Ecology and management of the African buffalo - Caron, Alexandre 1975- (Cambridge University Press, 2023)
One of iconic Africa's Big Five, the African buffalo is the largest African bovine or antelope that occurs throughout most of sub-Sahara and in a wide range of ecosystems from savanna to rainforest. The African buffalo is also one of the most successful large African mammals in terms of abundance and biomass. This species thus represents a powerful model to enhance our understanding of African biogeography and wildlife conservation, ecology and management. Edited by four researchers experienced in different aspects of the African buffalo's biology, this volume provides an exhaustive compilation of knowledge on an emblematic species that stands out as an important component of African natural and human ecosystems. It delivers a global view of the African buffalo and all known aspects of its ecology and management. This book will appeal to students, scholars, scientists and wildlife managers as well as those enthusiastic about the charismatic species. This title is also available as Open Access on Cambridge Core.